Implant considerations for patients with periodontitis - YANG Ze, PAN Yaping (Kouqiang yixue)
Periodontitis is a clear risk factor for peri-implant diseases, so implant therapy for patients with periodontitis is special and difficult. It is important to control periodontal infection before implant placement. Besides, we should choose the appropriate surgical procedures and protocols according to the anatomical characteristics of different regions. After implant surgery, we should provide periodontal care to maintain the health and long-term stability of the natural teeth and the implants. This article summarizes and reviews the pathogenic characteristics of periodontitis and the characteristics of hard and soft tissues after infection. It systematically describes how implant treatment should be considered and maintained in the therapeutic process, which provides reference for clinical treatment.